Utility of p16 Immunohistochemistry in Evaluating Negative Cervical Biopsies Following High-risk Pap Test Results. (January 2018) - Shain, Alana F.; Kwok, Shirley; Folkins, Ann K.; Kong, Christina S.
Abstract : The Lower Anogenital Squamous Terminology (LAST) Standardization Project for human papilloma virus (HPV)-associated lesions specifically recommends the use of p16 immunohistochemistry (IHC) as an adjunct to morphologic assessment of cervical biopsies interpreted as negative or low-grade squamous intraepithelial lesion (LSIL) from patients with prior high-risk Pap test results (high-grade squamous intraepithelial lesion [HSIL], atypical squamous cells cannot exclude HSIL, atypical glandular cells [AGC], or HPV16 + atypical squamous cells of undetermined significance [ASC-US]). The impetus for this recommendation is to increase detection of missed high-grade disease. However, the quality of evidence supporting this recommendation was lower than that for the other LAST recommendations addressing improved consistency in the diagnosis of HSIL with the use of p16. A database search spanning 10 years identified 341 cases (encompassing 736 discrete biopsy specimens) interpreted as negative for dysplasia from 330 patients with a prior high-risk Pap result (atypical squamous cells cannot exclude HSIL, HSIL, atypical glandular cells, not otherwise specified [AGC-NOS], atypical endocervical cells–NOS [AEC-NOS], and AEC-favor neoplastic). p16 IHC was performed and detected missed abnormalities in 11/341 (3.2%) cases. The abnormalities corresponded to missed foci of HSIL (cervical intraepithelial neoplasia [CIN] 2) (n=1), SIL-indeterminate grade (n=7), atypical squamous metaplasia (n=2), and LSIL [CIN1]) (n=1). Subsequent histologic follow-up identified HSIL or greater in 6/8 (75%) p16 + cases versus 20/79 (25.3%) p16 − cases ( P =0.0079). p16 IHC performed on biopsies interpreted as negative from patients with prior high-risk Pap test results increased the detection rate of missed SIL. A p16 + result also significantly increased the likelihood of HSIL on subsequent biopsy. Although further studies are required to determine what percentage of missed HSIL justifies the additional cost, improved detection of HSIL in high-risk patients may lead to fewer diagnostic procedures and fewer patients lost to follow-up.